Comparative study of the in-plane uniaxial and biaxial crushing of hexagonal, re-entrant, and mixed honeycombs. (September 2019) - Li, Zhen; Gao, Qiang; Yang, Sen; Wang, Liangmo; Tang, Jun
The in-plane uniaxial and biaxial crushing characteristics of three honeycombs were studied through explicit dynamic finite element analysis in this paper. Crushing models were created, with all square specimens (hexagonal, reentrant and mixed honeycombs) deliberately built in the same scale. The in-plane uniaxial compressive performances of cellular structures in terms of the deformation mode, plateau stress, energy absorption as well as the impact response were compared and discussed, respectively. In the same loading condition, these honeycombs exhibited distinct characteristics. After that, in-plane orthogonal biaxial crushing simulations were carried out. Deformation processes of honeycombs were analyzed and compared. Results illustrated that some deformation behaviors in the uniaxial crushing case still exist in the biaxial crushing analysis. Their deformation modes were drawn into deformation maps. Energy absorption research illustrated that the transverse shrinking property in the uniaxial crushing case was detrimental to the energy dissipation capacity of honeycomb in the biaxial crushing case. In addition, comparing with the hexagonal honeycomb, reentrant honeycomb with slightly thicker cell walls expressed weaker ability in specific energy dissipation.